Ultra-broadband near-infrared photoluminescence in Er3+-Ni2+co-doped transparent glass ceramics containing nano-perovskite KZnF3. Issue 16 (November 2020) - Wang, Xin; Wang, Pengfei; Zhao, Haiyan; Tian, Ke; Jia, Shijie; Wang, Shunbin; Brambilla, Gilberto
Abstract: In this article, ultra-broadband photoluminescence in near-infrared is achieved in KZnF3 glass ceramics doped with Er 3+ and Ni 2+ ions. Er 3+ -Ni 2+ co-doped fluorosilicate glass and glass ceramics embedded with perovskite nanocrystals were fabricated and efficient energy transfer (ET) from Er 3+ to Ni 2+ ions was confirmed by luminescence spectra and decay curves. In the glass ceramic samples, Ni 2+ ions were effectively sensitized by Er 3+, and ultra-broadband photoluminescence from 1400 to 2300 nm was observed when a 980 nm laser was used as a pump, as shown in Fig. 1. The temperature and humidity stability of the glass ceramic samples was characterized from the measured transmittance. These results demonstrated that Ni 2+ -Er 3+ co-doped glass ceramics have significant potential for application in optical communication and broadband amplifiers.